Answer:
x < -12
Step-by-step explanation:
Given the inequality
-2(x + 3) < 6 - x
Expand
-2x - 6 < 6 - x
Collect the like terms;
-2x + x < 6 + 6
-x < 12
Multiply through by -1
-1(-x) < -1(12)
x < -12
Step-by-step explanation:
4x2 - 25b2
We can solve it by the squares so
(2x - 5b) (2x + 5b)
2) x2 - 81
The same case is here so
(x - 9) (x + 9)
The missing number is 6. 3.6-.65 = 2.95
3.6 - 2.95 = .65
Hope it helps ;)))
PEMDAS so you do 3*4 which equals 12, then you add 8=20 20/2=10
There are 5 less black kittens than there are gray. 7 - 2 = 5
Hope this helps! Let me know if you need any further assistance!